2003
DOI: 10.1074/jbc.m212756200
|View full text |Cite
|
Sign up to set email alerts
|

Extended Core 1 and Core 2 Branched O-Glycans Differentially Modulate Sialyl Lewis x-type L-selectin Ligand Activity

Abstract: It has been established that sialyl Lewis x in core 2 branched O-glycans serves as an E-and P-selectin ligand. Recently, it was discovered that 6-sulfosialyl Lewis x in extended core 1 O-glycans, NeuNAc␣233Gal-␤134(Fuc␣133(sulfo36))GlcNAc␤13 3Gal␤133Gal-NAc␣13 Ser/Thr, functions as an L-selectin ligand in high endothelial venules. Extended core 1 O-glycans can be synthesized when a core 1 extension enzyme is present. In this study, we first show that ␤1,3-N-acetylglucosaminyltransferase-3 (␤3GlcNAcT-3) is almo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
1
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 51 publications
2
54
1
1
Order By: Relevance
“…13,37 It is proposed that glycosyltransferases are organised in the same order in which they act; such that those acting early in glycan biosynthesis are localised to the cis and medial compartments, whereas enzymes acting later tend to localize to the transGolgi cisternae and the trans-Golgi network (reviewed in 38 ). Accordingly, the sLe x -specific a(2,3)-sialyltransferases (denoted as ST3GalTs) have been proposed to localize to the late Golgi compartments 39,40 and our earlier studies have shown that FUT1 overlaps very well with the a-mannosidase-II and the core2 b(1,6)-N-acetyglucosaminyltransferase (C2GnT-I) in the cis/ medial Golgi compartments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,37 It is proposed that glycosyltransferases are organised in the same order in which they act; such that those acting early in glycan biosynthesis are localised to the cis and medial compartments, whereas enzymes acting later tend to localize to the transGolgi cisternae and the trans-Golgi network (reviewed in 38 ). Accordingly, the sLe x -specific a(2,3)-sialyltransferases (denoted as ST3GalTs) have been proposed to localize to the late Golgi compartments 39,40 and our earlier studies have shown that FUT1 overlaps very well with the a-mannosidase-II and the core2 b(1,6)-N-acetyglucosaminyltransferase (C2GnT-I) in the cis/ medial Golgi compartments.…”
Section: Discussionmentioning
confidence: 99%
“…11 HepG2 cells infected with particles of pRRLpgk-GFP.sin18 to express EGFP alone are denoted as parental cells throughout the manuscript. The construct for E-selectin conjugated to the human IgM portion 13 (denoted as E-selectin-IgM chimera) was kindly provided by Dr Minoru Fukuda (The Burnham Institute, La Jolla, CA). The E-selectin-IgM chimera was produced by transiently transfecting the human 293-T cells as described.…”
Section: Cell Lines Dnas and Lentiviral Transductionmentioning
confidence: 99%
“…For this assay, PC3 and LNCaP cells in cloning plates were dissociated into monodispersed cells using an enzyme-free dissociation solution (Hanks' balanced saline solution-based) purchased from Cell and Molecular Technologies. Dissociated cells were incubated with fluorescein isothiocyanate-conjugated PNA and subjected to fluorescence-activated cell sorting analysis using FACScan flow cytometry (BD Biosciences) as described previously (26). As controls, PC3 and LNCaP cells were transfected with empty pcDNA 3.1(N) and pcDNA 3 and selected in Geneticin.…”
Section: Experimental and Proceduresmentioning
confidence: 99%
“…cDNA encoding core3 synthase (␤3GlcNAcT-6) (15) was amplified by reverse transcription (RT)-PCR and cloned into pcDNA 3.1(N) as described previously (26). pcDNA 3.1(N) was prepared by deleting the Zeocin resistance gene and f1 origin from pcDNA 3.1/Zeo as described previously (26). PC3 and LNCaP cells were transfected with pcDNA 3.1(N) harboring core3-synthase cDNA and pcDNA 3 harboring the neomycin resistance gene using Lipofectamine.…”
Section: Experimental and Proceduresmentioning
confidence: 99%
“…Mounting evidence indicates these features are accommodated in the capping group 6-sulfo sLex in which the sLex tetrasaccharide (Sia␣2,3Gal␤1,4-[Fuc␣1,3] GlcNAc) is modified with sulfation on the C-6 position of GlcNAc (7)(8)(9). This structure can be presented as the terminus of both a core-2 branch and an extended core-1 branch of an O-glycan, and contributes to ligand activity in both positions (9,10). A potential role for Gal-6-sulfate has also been suggested for ligands in the mouse, but the structural context for this modification is presently unknown (7,11).…”
mentioning
confidence: 99%